Korelasi Antara Persepsi Mahasiswa Tentang Profesi Keguruan dan Adversity Intelligence Dengan Minat Menjadi Guru - Ica Motiara; Retno Mustika Dewi (Universitas Negeri Surabaya, 2022)
This study aims to examine the relationship between student perceptions of the teaching profession and adversity intelligence with interest in becoming a teacher at the 2018 State University of Surabaya State University Economics Department Students. The type of research used is quantitative associative research. The data collection technique used was by using a questionnaire distributed to all samples collected by 153 JPE students at the State University of Surabaya in 2018 obtained through the slovin formula. This study uses data analysis techniques that include prerequisite analysis and hypothesis testing (Pearson correlation test and multiple correlation analysis) through the SPSS application. The results of this study indicate: 1) Partially, student perceptions of the teaching profession have a positive and significant relationship with interest in becoming a teacher, 2) Partially, adversity intelligence has a positive and significant relationship with interest in becoming a teacher, 3) Simultaneously, student perceptions about the teaching profession and adversity intelligence have a positive and significant relationship with interest in becoming a teacher.